2002
DOI: 10.1021/jp013533i
|View full text |Cite
|
Sign up to set email alerts
|

In Situ IR Observation of Surface Species during the Photocatalytic Decomposition of Acetic Acid over TiO2 Films

Abstract: Surface-enhanced IR absorption spectroscopy (SEIRAS) was applied to in-situ observation of the adsorption states and the photocatalytic decomposition of acetic acid on Au/TiO2 and Au/Pt/TiO2 films. The adsorption states of acetic acid were determined in both the liquid and gas phase, and molecular adsorption was found to be dominant in the gas phase. Pt deposition on the TiO2 film led to the formation of adsorbed methyl during the photodecomposition of gas-phase acetic acid, indicative of the formation of meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 21 publications
2
20
0
Order By: Relevance
“…105 Similarly, the photocatalytic decomposition of acetic acid, both in liquid and vapor phase, using TiO 2 has been investigated in SEI-RA. 106 The feasibility of in situ ATR-SEIRA spectroscopy for the study of liquid-phase heterogeneous catalysis by platinum metals has also been reported. 107 Electrochemistry.…”
Section: Applications Of Surface-enhanced Infrared Absorptionmentioning
confidence: 99%
“…105 Similarly, the photocatalytic decomposition of acetic acid, both in liquid and vapor phase, using TiO 2 has been investigated in SEI-RA. 106 The feasibility of in situ ATR-SEIRA spectroscopy for the study of liquid-phase heterogeneous catalysis by platinum metals has also been reported. 107 Electrochemistry.…”
Section: Applications Of Surface-enhanced Infrared Absorptionmentioning
confidence: 99%
“…Some of the research tends to speculate the chemical reaction path of photocatalysis indirectly by ''in situ'' monitoring the transformation of functional groups on TiO 2 during photocatalytic process by using a Fourier transform infrared (FTIR) spectroscopy. [4][5][6][7][8][9][10][11][12][13] But the variation of structure and electronic states of TiO 2 during photocatalyzing can not be known from this indirect method. One the other hand, the changes in the surface lattice of TiO 2 by photo-induced had been researched.…”
Section: Introductionmentioning
confidence: 99%
“…When the molecules are adsorbed on nanoparticle metal films, the infrared absorption of molecules is enhanced, this phenomenon is called surface-enhanced infrared absorption (SEIRA) [1][2][3]. SEIRA can provide several orders of magnitude enhancement of modes in the IR region and has been successfully used in surface catalysis [4], analytical chemistry [5], biochemistry [6], sensor [7], metal corrosion [8], and surface photochemistry [9]. According to current research, the enhancement of IR is highly dependent on the morphology of the nanoparticles such as size [10], spacing [11], and thickness [12], as well as the polarization direction of incident light [13] and dielectric property of the metal [14].…”
Section: Introductionmentioning
confidence: 99%